Degradable micro-emulsified water-based cutting fluid special for heavy-load copper alloy as well as preparation method and application of degradable micro-emulsified water-based cutting fluid
By using biodegradable vegetable oil and ammonium phosphate salts as lubricants, and optimizing the composition and preparation process of copper alloy processing fluids, the problems of insufficient lubrication and corrosion resistance of copper alloy processing fluids were solved, achieving efficient and environmentally friendly copper alloy processing.
Patent Information
- Application Number
- CN202511189280.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2025-12-02
AI Technical Summary
Existing copper alloy processing fluids are inadequate in terms of lubrication, corrosion resistance, and friction performance, and are prone to deterioration after prolonged use, leading to environmental pollution and health risks to workers.
Using green, environmentally friendly, biodegradable vegetable oil and ammonium phosphate as lubricants, combined with special amines, metal rust inhibitors and other components, and through optimized preparation process, a microemulsion water-based cutting fluid with high load-bearing capacity and high lubrication performance is formed.
It improves the lubrication and corrosion resistance of copper alloy machining fluid, extends its service life, reduces environmental hazards, and is suitable for high-precision copper alloy machining.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metalworking fluid technology, specifically relating to a heavy-duty biodegradable microemulsion water-based cutting fluid for copper alloys, its preparation method, and its application. Background Technology
[0002] With the booming development of the machinery manufacturing industry, the demand for high-precision metal processing is constantly increasing. The increasingly stringent environmental regulations and the continuous emergence of technological innovations are making metalworking fluids more efficient, environmentally friendly and intelligent, thereby continuously driving the development of the metalworking fluid market.
[0003] Metalworking fluids are mainly used for lubrication, cooling, rust prevention and cleaning in metal cutting, grinding and forming processes, and have become an indispensable auxiliary material in modern machinery manufacturing.
[0004] Microemulsions are a new type of cutting fluid that falls between emulsions and synthetic fluids. Following emulsion and synthetic cutting fluids, they represent a new generation of water-based cutting fluids. They are microemulsions formed by highly diluting microemulsion oil with water. Microemulsions overcome the shortcomings of emulsions, such as easy spoilage and poor cleaning performance, as well as the corrosion of machine tool paint and poor lubrication performance of synthetic cutting fluids. They combine the advantages of both emulsions and synthetic fluids, exhibiting excellent extreme pressure, lubrication, cooling, rust prevention, and cleaning capabilities. Their lower cost makes them a major development direction for future metalworking fluids.
[0005] In the existing technology, there are also many microemulsion cutting fluids used for metal processing. For example, Chinese Patent Publication No. CN117229839A discloses a water-soluble metalworking fluid for aerospace composite materials and its preparation process. Through optimized compounding of softened water, graphite powder, and other additives, it achieves superior lubricity, resulting in extremely high surface finish and good cooling performance on the machined workpiece. Another example is Chinese Patent Publication No. CN118853270A, which discloses a copper alloy cutting fluid. By adding rust inhibitors and corrosion inhibitors, it can improve the rust prevention, lubrication, and corrosion inhibition performance of copper alloys during machining. Chinese Patent Publication No. CN104450097A discloses a metalworking fluid suitable for copper alloys, which is prepared by mixing organic alcohol amines, emulsifiers, lubricants, and other substances. The aforementioned metalworking fluid for copper alloys has good rust prevention and lubrication performance, making it suitable for high-temperature casting.
[0006] While existing metal cutting fluids possess good stability and lubrication properties, their tribological properties are poor and their costs are high. Even so, the problem of long-term fluid deterioration remains unresolved, leading to serious waste issues, environmental pollution, and risks of worker injury.
[0007] Copper and its alloys are characterized by low strength and hardness, high plasticity, and good ductility. They also possess excellent thermal and electrical conductivity, making them widely used in automotive electronics, aerospace, smart homes, machine tools, and other fields. Copper is one of the most widely used non-ferrous metals in my country. With the rapid development of these fields, the demand for processing copper and copper alloys is increasing. One common problem encountered during copper processing is the greening of the cutting fluid, sometimes resulting in the precipitation of green substances that adhere to the fixtures or inner glass surfaces. This often makes it difficult to observe the copper processing process, and the finished product is difficult to clean, sometimes even leading to corrosion.
[0008] To address the above issues, the development and production of microemulsion cutting fluids for copper alloys require consideration of their lubrication, cooling, and corrosion resistance. Microemulsion cutting fluids typically use refined mineral oil as the base oil and high-lubricity extreme pressure agents as the main lubricating components to ensure the gloss and precision of the machined surface.
[0009] Based on this, this invention, taking into account the multi-functionality of low foaming, environmental protection, lubrication, and cooling, and addressing the requirements of existing copper alloy processing technology for water-based cutting fluids, develops a low-sulfur and low-phosphorus water-based microemulsion cutting fluid for copper alloys with high load-bearing capacity and high lubrication performance, in order to improve the lubrication performance, corrosion resistance, and friction performance of cutting fluids. Summary of the Invention
[0010] To address the shortcomings of existing technologies, the present invention aims to provide a heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid and its preparation method. By selecting green and environmentally friendly biodegradable vegetable oil and synthetic ester as the main lubricants and ammonium phosphate salt as the extreme pressure anti-wear agent, the invention solves the problems of poor lubrication performance, short life, high hazard, and easy green corrosion in copper alloy metalworking fluids prepared by existing technologies.
[0011] This invention optimizes and adjusts the raw materials and preparation process of the cutting fluid to ensure that each component is uniformly dispersed in water and works synergistically. This results in a microemulsion water-based cutting fluid with excellent lubrication, corrosion resistance, and friction properties, making it suitable for high-load machining of copper alloys.
[0012] This invention also provides the application of the aforementioned heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid.
[0013] To achieve the above-mentioned technical objectives, the present invention adopts the following technical solution:
[0014] A heavy-duty, biodegradable, microemulsion-based water-based cutting fluid for copper alloys is prepared from the following raw materials in parts by weight: 4.0–8.0 parts metal rust inhibitor; 10.0–18.0 parts special amine; 5.0–10.0 parts synthetic ester; 0.5–1.0 parts extreme pressure agent; 5.0–10.0 parts lubricant; 0.5–1.0 parts corrosion inhibitor; 1.0–2.0 parts dispersant; 0.5–2.5 parts bactericide; 2.0–6.0 parts stabilizer; 5.0–10.0 parts emulsifier; 0.4–1.0 parts anti-hard water agent; and 45–50 parts water.
[0015] Specifically, the special amine is one or more of the following: special amine V-20 (2,2'-(cyclohexylimino)diethanol), special amine AMP-95 (2-amino-2-methyl-1-propanol), special amine AM101, special amine SA166, and diethylene glycol amine. This invention can also use combinations of various special amines to replace traditional organic alcohol amine combinations, thereby controlling the risk of corrosion to non-ferrous metals and alloys at the source, extending the fluid change cycle, and improving the service life of the metalworking fluid.
[0016] Specifically, the corrosion inhibitor is one or more of benzotriazole, alkyl phosphate, methylbenzotriazole, thiadiazole, and aluminum zinc magnesium corrosion inhibitor.
[0017] Specifically, the metal rust inhibitor is one or more of sebacic acid, phosphate ester, borate ester, and dodecanoic acid.
[0018] Specifically, the lubricant is one or more of vegetable oil, base oil, naphthenic oil, polyether, and ethylene oxide-propylene oxide block copolymer.
[0019] Specifically, the dispersant is an alcohol ether carboxylic acid (specifically, the brand name HW08).
[0020] Specifically, the bactericide is one or more of MBK (oxazoline heterocyclic compound), MBM (N,N'-methylenebismorpholine), NS-MBM (bismorpholine methane derivative), MBO (3,3'-methylenebis(5-methyloxazoline)), BK (1,3,5-tris(2-hydroxyethyl)-hexahydrotriazine), and BIT (1,2-benzisothiazolin-3-one).
[0021] Furthermore, the extreme pressure agent is a phosphorus-nitrogen type extreme pressure anti-wear agent (specifically, an ammonium phosphate salt), or the extreme pressure agent is a water-soluble phosphate ester.
[0022] Furthermore, the stabilizer is one or more of Tween 20, Tween 40, Tween 60, Tween 80, Span 20, Span 40, Span 60, and Span 80.
[0023] Furthermore, the emulsifier is one or more of succinic anhydride amide, tallowamide, and tallow diethanolamide.
[0024] Furthermore, the anti-hard water agent is tetrasodium ethylenediaminetetraacetate.
[0025] Furthermore, the synthetic ester is one or more of the following: tetrameric castor oil ester, pentaerythritol oleate, trimethylolpropane oleate, trimethylolpropane coconut oil ester, diisooctyl sebacate, neopentyl glycol oleate, and isooctyl stearate.
[0026] This invention further enhances the copper alloy metalworking fluid by adjusting the types and amounts of components such as special amines, metal rust inhibitors, environmentally friendly biodegradable lubricants, dispersants, corrosion inhibitors, hard water agents, and bactericides, thereby improving its lifespan. Furthermore, the special formulation of corrosion inhibitors reduces the likelihood of green corrosion.
[0027] Furthermore, based on a general inventive concept, the present invention also provides a method for preparing the aforementioned ammonium phosphate salt extreme pressure agent, comprising the following steps:
[0028] 1) A certain amount of isodecyl alcohol is added to the reaction vessel and pre-stirred. Phosphorus pentoxide and water are added and stirred continuously to prevent agglomeration. An esterification reaction occurs at a certain temperature to obtain a phosphate intermediate.
[0029] 2) Then, alkylamine is added dropwise to the phosphate intermediate, and an amination reaction occurs at a certain temperature. Unreacted raw materials and byproducts are then removed by vacuum distillation to obtain ammonium phosphate salt.
[0030] The yield of the ammonium phosphate salt is greater than 99%, the product has high nitrogen and phosphorus content, good low-temperature fluidity, does not solidify, does not require the use of organic solvents, and can reduce harm to the environment and human health.
[0031] Specifically, in step 1), the water is tap water, and the amount used is 5wt%-10wt% of the total amount of isodecanol, phosphorus pentoxide and water.
[0032] Specifically, in step 1), the pre-stirring temperature is 0-20℃ and the time is 10-30min.
[0033] Specifically, in step 1), the esterification reaction is carried out at a temperature of 60-90°C for 3-6 hours.
[0034] Specifically, in step 2), the amination reaction is carried out at a temperature of 100-130°C for 3-6 hours.
[0035] Specifically, in step 2), the temperature of the vacuum distillation is 80-130℃, and the time is 0.5-1h.
[0036] Specifically, in step 2), the alkylamine is one or more of the following: tertiary alkyl primary amine (PRIMENE 81RCAS:68955-53-3), oleylamine (CAS:112-90-3), and dodecylamine (CAS:124-22-1).
[0037] Specifically, the molar ratio of phosphorus pentoxide, isodecanol, and alkylamine used in the synthesis of the ammonium phosphate salt is 0.5-1:2-3:0.5-0.9.
[0038] Furthermore, based on a general inventive concept, the present invention also provides a method for preparing a heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid, comprising the following steps:
[0039] S1: Add special amine, metal rust inhibitor and a portion of water to the reactor, and heat and stir at 45-65°C until the solution becomes clear;
[0040] S2: Add the emulsifier, extreme pressure agent, lubricant and synthetic ester to the solution obtained in step S1, and continue heating and stirring until the solution becomes clear;
[0041] S3: Add the stabilizer and the anti-hard water agent to the solution obtained in step S2, and continue heating and stirring until the solution becomes clear;
[0042] S4: After the temperature of the solution obtained in step S3 drops to 10-35°C, add the dispersant and bactericide to the solution and stir until transparent;
[0043] S5: Add the corrosion inhibitor to the solution obtained in step S4, stir until transparent, add another part of water, mix and stir to obtain microemulsion water-based cutting fluid.
[0044] Specifically, in step S1, the mass ratio of the special amine, the metal rust inhibitor, and the water is (10.0-18.0):(4.0-8.0):(17.0-20.0); preferably (16.0-18.0):(5.0-6.0):20.0.
[0045] Specifically, in step S2, the mass ratio of emulsifier, extreme pressure agent, lubricant, and synthetic ester is (5.0~10.0):(0.5~1.0):(5.0~10.0):(5.0~10.0); preferably 6.0:1.0:(5.0~8.0):(8.0~10.0).
[0046] Specifically, in step S3, the mass ratio of stabilizer to anti-hard water agent is (2.0-6.0):(0.4-1.0); preferably (3.0-6.0):0.8.
[0047] Specifically, in step S4, the mass ratio of dispersant to bactericide is (1.0-2.0):(0.5-2.5); preferably 1.5:(1.5-1.8).
[0048] Specifically, in step S5, the mass ratio of corrosion inhibitor to water is (0.5-1.0):(28.0-30.0); preferably (0.8-1.0):29.0.
[0049] Specifically, in step S1, the stirring temperature is 50-60℃ and the stirring time is 0.2-1h; the preferred stirring temperature is 55℃ and the preferred stirring time is 0.5h.
[0050] Specifically, in step S2, the stirring temperature is 45-65℃ and the stirring time is 0.2-1h; the preferred stirring temperature is 55℃ and the preferred stirring time is 0.5h.
[0051] Specifically, in step S3, the stirring temperature is 45-65℃ and the stirring time is 0.2-1h; the preferred stirring temperature is 55℃ and the preferred stirring time is 0.2-0.5h, more preferably 0.2h.
[0052] Specifically, in step S4, the stirring temperature is room temperature (25±5℃); the stirring time is 0.2 to 1 hour, preferably 0.2 to 0.5 hours, and more preferably 0.3 hours.
[0053] Specifically, in step S5, the stirring time until transparent is 0.2 to 0.5 hours, and the temperature is 55 to 65 degrees Celsius; the mixing time is 0.5 to 1 hour.
[0054] Specifically, the heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid can be diluted with tap water or well water to form a working fluid before use.
[0055] Specifically, during dilution, the cutting fluid is diluted with water to a working solution concentration of 5-20 wt%, preferably 5 wt%, 10 wt%, or 20 wt%.
[0056] Furthermore, based on a general inventive concept, the present invention also provides a heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid prepared using the above method.
[0057] Furthermore, based on a general inventive concept, the present invention also provides the application of the aforementioned heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid in metal cutting or grinding processes.
[0058] Specifically, the cutting object is one or more of copper alloys, zinc-copper alloys, nickel-copper alloys, and tin-copper alloys; copper alloys are preferred.
[0059] Compared with the prior art, the advantages of the present invention are:
[0060] This invention uses biodegradable vegetable oil as a lubricant, ammonium phosphate salt as an extreme pressure anti-wear agent, and combines it with special amines, metal rust inhibitors, and tetrameric castor oil ester with excellent lubrication properties. The resulting microemulsion water-based cutting fluid has good lubrication performance and high load-carrying capacity.
[0061] Tribological performance evaluation showed that after the microemulsion water-based cutting fluid was prepared into a 5wt% diluted solution, the maximum non-seize load P B The value can reach 1569N; when the cutting fluid dilution concentration is increased to 10%, the maximum non-seize load P B The value can reach 1667N; the coefficient of friction is below 0.1 under a 510N load, and when the dilution concentration of the cutting fluid is increased to 10wt%, the coefficient of friction is below 0.07.
[0062] Compared with commercially available well-known domestic and international brands, the tapping torque value of the microemulsion water-based cutting fluid prepared in this invention is comparable to that of Fuchs (EcoCool 68S) and three domestic brands. This indicates that the microemulsion water-based cutting fluid prepared in this invention has excellent machining performance when machining copper alloy workpieces and is suitable for machining high-precision, high-hardness copper and copper alloy workpieces.
[0063] The preparation method of the present invention is simple to operate, low in cost, the diluent is easy to clean and environmentally friendly, the experiment does not require expensive instruments and equipment, it is easy to realize large-scale mass production, and has important application potential.
[0064] The ammonium phosphate extreme pressure additive of this invention is a phosphate amine salt compound synthesized via a two-step method. Its molecular structure contains both phosphorus and nitrogen active elements. This additive forms a stable extreme pressure lubricating film on the metal surface through a chemical adsorption mechanism, significantly improving the tribological properties of the cutting fluid under high load conditions. The maximum non-seize load (P0) of the prepared microemulsion water-based cutting fluid was measured using a four-ball friction tester. B The extreme pressure (XP) value can reach 1667 N, exhibiting excellent extreme pressure anti-wear performance. Experimental results show that the microemulsion water-based cutting fluid prepared in this invention has the following outstanding advantages in the cutting and machining of copper alloys: (1) excellent extreme pressure lubrication performance, which can meet the requirements of heavy-duty machining conditions; (2) good corrosion inhibition performance of copper alloys; (3) stable microemulsion system; (4) outstanding machining accuracy control capability. This cutting fluid has excellent comprehensive performance and has important engineering application value and industrialization prospects in the field of precision machining of copper alloys. Attached Figure Description
[0065] Figure 1The images shown are optical images of the microemulsion water-based cutting fluids obtained in Examples 1-5 (corresponding to ae in the figure) and Comparative Examples 1-4 (corresponding to fi in the figure).
[0066] Figure 2 The figure shows the maximum non-seize load (P) of the microemulsion water-based cutting fluid diluents obtained in Examples 1-5 and 10, and the 5wt% diluents of Comparative Examples 1-4, in a four-ball test. B Value data chart;
[0067] Figure 3 The figure shows a comparison of the friction coefficients of the microemulsion cutting fluids obtained in Examples 1-5 and the 5wt% diluted solutions of Comparative Examples 1-4 in a four-ball friction experiment (room temperature, load 510N, rotation speed 1450r / min, long grinding for 30min).
[0068] Figure 4 The figure shows a comparison of the wear scar diameters of the microemulsion cutting fluids obtained in Examples 1-5 and the 5wt% diluted solutions of Comparative Examples 1-4 in a four-ball friction experiment (room temperature, load 510N, rotation speed 1450r / min, long grinding for 30min).
[0069] Figure 5 The images shown are optical images of the copper corrosion test specimens (55°C, 8h) of the microemulsion cutting fluids obtained in Examples 1-5 and the 5wt% dilutions of Comparative Examples 1-4.
[0070] Figure 6 The images shown are optical images of the microemulsion cutting fluids obtained in Examples 1-5 and 5wt% diluents of Comparative Examples 1-4 after copper corrosion testing (55°C, 8h).
[0071] Figure 7 The image shown is an optical image of a cast iron specimen (35°C, 24h) of a 5wt% diluted microemulsion cutting fluid obtained in Example 5.
[0072] Figure 8 The image shown is an optical image of a cast iron stack test piece (35°C, 4h) of a 5wt% diluted microemulsion cutting fluid obtained in Example 5.
[0073] Figure 9 The image shown is an optical image of the defoaming performance test of the 5wt% diluted microemulsion cutting fluid obtained in Example 5. Detailed Implementation
[0074] The technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0075] Unless otherwise specified, all instruments and equipment used in the following examples are commercially available standard instruments and equipment; all other reagents and materials used are commercially available standard reagents and materials. Unless otherwise specified, all experimental methods involved in the following examples are conventional methods.
[0076] In the following examples and comparative examples, room temperature refers to 25±5℃.
[0077] In the following examples, the number of portions refers to the number of weight portions, that is, the number of portions in the following examples corresponds to the number of grams.
[0078] Example 1
[0079] Example 1 provides a heavy-duty, biodegradable, microemulsion-based water-based cutting fluid specifically for copper alloys, prepared from the following raw materials:
[0080] Specialty amines, corrosion inhibitors, metal rust inhibitors, lubricants, dispersants, bactericides, synthetic esters, stabilizers, emulsifiers, hard water inhibitors, extreme pressure agents, and deionized water.
[0081] The extreme pressure agent described in Example 1 is a phosphorus-nitrogen type extreme pressure anti-wear agent, specifically an ammonium phosphate salt, which is prepared through the following steps:
[0082] 1) A certain amount of isodecanol was added to a three-necked flask and pre-stirred. Phosphorus pentoxide and water were added and stirred continuously to prevent agglomeration. An esterification reaction was carried out at a certain temperature to obtain a phosphate intermediate.
[0083] 2) Then, alkylamine is added dropwise to the phosphate intermediate, and an amination reaction occurs at a certain temperature. Unreacted raw materials and byproducts are then removed by vacuum distillation to obtain ammonium phosphate salt.
[0084] The yield of the ammonium phosphate salt is greater than 99%, the product has high nitrogen and phosphorus content, good low-temperature fluidity, does not solidify, does not require the use of organic solvents, and can reduce harm to the environment and human health.
[0085] In step 1), the water is tap water, and the amount used is 8 wt% of the total amount of isodecanol, phosphorus pentoxide, and water.
[0086] In step 1), the pre-stirring temperature is 10°C and the time is 20 min.
[0087] In step 1), the esterification reaction is carried out at a temperature of 80°C for 5 hours.
[0088] In step 2), the amination process is carried out at a temperature of 120°C for 3 hours.
[0089] In step 2), the temperature of the vacuum distillation is 100°C and the time is 1 hour.
[0090] In step 2), the alkylamine is a tertiary alkyl primary amine (PRIMENE 81RCAS:68955-53-3).
[0091] The molar ratio of phosphorus pentoxide, isodecanol, and alkylamine used in the synthesis of the ammonium phosphate salt is 1:3:0.9, and all the above reagents are of industrial grade purity.
[0092] The equipment and other process parameters used in the vacuum distillation of this invention can be set using conventional methods in the prior art, and are not the inventive point of this invention, so they will not be described in detail here.
[0093] The heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid described in Example 1 was prepared through the following steps:
[0094] S1: Add 18.0 parts of special amine V-20 (specifically 2,2'-(cyclohexylimino)diethanol), 6.0 parts of sebacic acid (Jinghua 99), and 20 parts of water to the reactor, and heat and stir at 55°C for 0.5 h until the solution becomes clear;
[0095] S2: Add 6.0 parts of succinic anhydride amide (PIBSA EH amide), 1 part of extreme pressure agent (ammonium phosphate salt), 5 parts of vegetable oil (specific brand XP600) and 10.0 parts of tetrameric ricinoleate to the solution obtained in step S1, and stir at 55°C for 0.5 h until the solution is transparent.
[0096] S3: Add 6.0 parts of Tween 20 and 0.8 parts of tetrasodium ethylenediaminetetraacetate to the solution obtained in step S2, and stir at 55°C for 0.2 hours until the solution becomes clear;
[0097] S4: After the temperature of the solution obtained in step S3 drops below 35°C (specifically 20-35°C), add 1.5 parts of alcohol ether carboxylic acid (specific brand HW08) and 1.5 parts of MBK (bactericide) to the solution, and stir at room temperature for 0.3 hours until transparent;
[0098] S5: Add 1.0 part of corrosion inhibitor (benzotriazole) to the solution obtained in step S4, stir at 60°C until transparent, add 29 parts of water, mix and stir for 1 hour to obtain cutting fluid.
[0099] The heavy-duty copper alloy biodegradable microemulsion water-based cutting fluid described in Example 1 was diluted with tap water with a hardness of 450 mg / L (calculated as CaCO3) to form a working solution for testing.
[0100] Specifically, during dilution, the cutting fluid is diluted with tap water to a concentration of 5 wt%, which is the working fluid of the heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid.
[0101] The performance testing method for the microemulsion water-based cutting fluid described in Example 1 is as follows, and the test is conducted on the diluted working fluid:
[0102] The tribological properties of the prepared cutting fluid were tested using a four-ball friction testing machine (MS-10A). The steel balls used in the test were GCr15 bearing steel balls with a diameter of φ = 12.7 mm. The test conditions were room temperature, load of 510 N, and rotational speed of 1450 r / min, measuring the coefficient of friction (COF) and the maximum non-seizure load (P) after 30 minutes of grinding. B The wear scar diameter on the steel ball surface was measured using an XDS-0745D optical microscope and a MicroXAM 3D non-contact surface tester.
[0103] A tapping torque testing system was used to test the tapping torque during the cutting or deformation process in metal processing. The test workpiece was a 7075# aluminum alloy nut with an inner diameter of 3.7mm and a high-precision titanium-plated extrusion tap of model 444-M5F-4.6. The test conditions were: rotation speed 300 r / min.
[0104] Example 2
[0105] Example 2 provides a heavy-duty biodegradable microemulsion water-based cutting fluid for copper alloys, which is prepared through the following steps:
[0106] S1: Add 18.0 parts of diethylene glycolamine (specific brand name CAS: 929-06-6), 6.0 parts of tricarboxylic acid (German MC) and 20 parts of water to the reactor, and heat and stir at 55°C for 0.5 h until the solution is clear;
[0107] S2: Add 6.0 parts talloamide (specific brand C4026), 1 part extreme pressure agent (water-soluble phosphate ester (specific brand EP270)), 5 parts vegetable oil (specific components are the same as in Example 1) and 10.0 parts tetrameric ricinoleate to the solution obtained in step S1, and stir at 55°C for 0.5 h until the solution is transparent.
[0108] S3: Add 6.0 parts of Span 80 and 0.8 parts of tetrasodium ethylenediaminetetraacetate to the solution obtained in step S2, and stir at 55°C for 0.2 h until the solution becomes clear;
[0109] S4: After the temperature of the solution obtained in step S3 drops below 35°C (specifically 20-35°C), add 1.5 parts of alcohol ether carboxylic acid (specific composition is the same as in Example 1) and 1.5 parts of MBM (bactericide) to the solution, and stir at room temperature for 0.3 hours until transparent;
[0110] S5: Add 1.0 part of corrosion inhibitor (methylbenzotriazole) to the solution obtained in step S4, stir at 60°C until transparent, add 29 parts of water, mix and stir for 1 hour to obtain cutting fluid.
[0111] Example 3
[0112] Example 3 provides a heavy-duty biodegradable microemulsion water-based cutting fluid for copper alloys, which is prepared through the following steps:
[0113] S1: Add 18.0 parts of special amine AMP-95 (specifically 2-amino-2-methyl-1-propanol), 6.0 parts of sebacic acid (Jinghua 99), and 20 parts of water to the reactor, and heat and stir at 55°C for 0.5 h until the solution becomes clear;
[0114] S2: Add 6.0 parts of succinic anhydride amide (same as in Example 1), 1 part of extreme pressure agent (ammonium phosphate salt (same as in Example 1)), 5 parts of vegetable oil (same as in Example 1) and 10.0 parts of tetrameric castor oil ester to the solution obtained in step S1, and stir at 55°C for 0.5 h until the solution is transparent;
[0115] S3: Add 6.0 parts of Tween 40 and 0.8 parts of tetrasodium ethylenediaminetetraacetate to the solution obtained in step S2, and stir at 55°C for 0.2 h until the solution becomes clear;
[0116] S4: After the temperature of the solution obtained in step S3 drops below 35°C (specifically 20-35°C), add 1.5 parts of alcohol ether carboxylic acid (specific composition is the same as in Example 1) and 1.5 parts of NS-MBM (bactericide) to the solution, and stir at room temperature for 0.3 hours until transparent;
[0117] S5: Add 1.0 part of corrosion inhibitor (methylbenzotriazole) to the solution obtained in step S4, stir at 60°C until transparent, add 29 parts of water, mix and stir for 1 hour to obtain cutting fluid.
[0118] The preparation of the extreme pressure agent in Example 3 is the same as in Example 1.
[0119] Example 4
[0120] Example 4 provides a heavy-duty biodegradable microemulsion water-based cutting fluid for copper alloys, which is prepared through the following steps:
[0121] S1: Add 18.0 parts of special amine AM101 (cyclohexylamine ethoxylate), 6.0 parts of tetracarboxylic acid (specifically NEUF985) and 20 parts of water to the reactor, and heat and stir at 55°C for 0.5 h until the solution is transparent;
[0122] S2: Add 6.0 parts tall oil diethanolamide (specific brand name DX2021), 1 part extreme pressure agent (ammonium phosphate salt (specifically the same as in Example 1)), 5 parts vegetable oil (specific composition same as in Example 1) and 10.0 parts tetrameric castor oil ester to the solution obtained in step S1, and stir at 55°C for 0.5 h until the solution is transparent.
[0123] S3: Add 6.0 parts of Span 80 and 0.8 parts of tetrasodium ethylenediaminetetraacetate to the solution obtained in step S2, and stir at 55°C for 0.2 h until the solution becomes clear;
[0124] S4: After the temperature of the solution obtained in step S3 drops below 35°C (specifically 20-35°C), add 1.5 parts of alcohol ether carboxylic acid (specific composition is the same as in Example 1) and 1.5 parts of MBM (bactericide) to the solution, and stir at room temperature for 0.3 hours until transparent;
[0125] S5: Add 1.0 part of corrosion inhibitor (methylbenzotriazole) to the solution obtained in step S4, stir at 60°C until transparent, add 29 parts of water, mix and stir for 1 hour to obtain cutting fluid.
[0126] The preparation of the extreme pressure agent in Example 4 is the same as in Example 1.
[0127] Example 5
[0128] Example 5 provides a heavy-duty biodegradable microemulsion water-based cutting fluid for copper alloys, which is prepared through the following steps:
[0129] S1: Add 18.0 parts of special amine SA166 (specific brand name CAS: 21829-52-7), 6.0 parts of sebacic acid (Jinghua 99), and 20 parts of water to the reactor, and heat and stir at 55°C for 0.5 h until the solution is clear;
[0130] S2: Add 6.0 parts of succinic anhydride amide (same as in Example 1), 1 part of extreme pressure agent (ammonium phosphate salt (same as in Example 1)), 5 parts of vegetable oil (same as in Example 1) and 10.0 parts of tetrameric castor oil ester to the solution obtained in step S1, and stir at 55°C for 0.5 h until the solution is transparent;
[0131] S3: Add 6.0 parts of Tween 20 and 0.8 parts of tetrasodium ethylenediaminetetraacetate to the solution obtained in step S2, and stir at 55°C for 0.2 hours until the solution becomes clear;
[0132] S4: After the temperature of the solution obtained in step S3 drops below 35°C (specifically 20-35°C), add 1.5 parts of alcohol ether carboxylic acid (specific composition is the same as in Example 1) and 1.5 parts of MBK (bactericide) to the solution, and stir at room temperature for 0.3 hours until transparent;
[0133] S5: Add 1.0 part of corrosion inhibitor (benzotriazole) to the solution obtained in step S4, stir at 60°C until transparent, add 29 parts of water, mix and stir for 1 hour to obtain cutting fluid.
[0134] The preparation of the extreme pressure agent in Example 5 is the same as in Example 1.
[0135] The dilution method and testing method of the microemulsion water-based cutting fluids in Examples 2-5 are the same as those in Example 1.
[0136] Example 6
[0137] Example 6 provides a heavy-duty biodegradable microemulsion water-based cutting fluid specifically for copper alloys. The preparation method of this cutting fluid is the same as that of Example 1. The difference between Example 6 and Example 1 is that when the cutting fluid of Example 6 is tested for performance, the load in the test conditions is reduced from 510N to 392N, while other conditions remain unchanged.
[0138] Example 7
[0139] Example 7 provides a heavy-duty biodegradable microemulsion water-based cutting fluid specifically for copper alloys. The preparation method of this cutting fluid is the same as in Example 1. The difference between Example 7 and Example 1 is that, during dilution, the cutting fluid is diluted with tap water to a concentration of 10 wt%, which is the working fluid of the heavy-duty biodegradable microemulsion water-based cutting fluid specifically for copper alloys. The testing methods and conditions are the same as in Example 1.
[0140] Example 8
[0141] Example 8 provides a heavy-duty biodegradable microemulsion water-based cutting fluid specifically for copper alloys. The preparation method of this cutting fluid is the same as that of Example 1. The difference between Example 8 and Example 1 is that when the cutting fluid of Example 8 is tested for performance, the load in the test conditions is increased from 510N to 696N, while other conditions remain unchanged.
[0142] Example 9
[0143] Example 9 provides a heavy-duty biodegradable microemulsion water-based cutting fluid specifically for copper alloys. The preparation method of this cutting fluid is the same as that of Example 5. The difference between Example 9 and Example 5 is that when the cutting fluid of Example 9 was tested, the load in the test conditions was reduced from 510N to 392N, while other conditions remained unchanged.
[0144] Example 10
[0145] Example 10 provides a heavy-duty biodegradable microemulsion water-based cutting fluid specifically for copper alloys. The preparation method of this cutting fluid is the same as in Example 5. The difference between Example 10 and Example 5 is that, during dilution, the cutting fluid is diluted with tap water to a concentration of 10 wt%, which is the working fluid of the heavy-duty biodegradable microemulsion water-based cutting fluid specifically for copper alloys. The testing methods and conditions are the same as in Example 5.
[0146] Comparative Example 1
[0147] Comparative Example 1 was a commercially available domestic microemulsion cutting fluid (C800). During testing, it was diluted with water to a concentration of 5 wt% for performance testing. The testing methods and conditions were the same as in Example 1.
[0148] Comparative Example 2
[0149] Comparative Example 2 used a commercially available domestic microemulsion cutting fluid (SCC101A). During testing, it was diluted with water to a concentration of 5 wt% for performance testing. The testing methods and conditions were the same as in Example 1.
[0150] Comparative Example 3
[0151] Comparative Example 3 was a commercially available domestic microemulsion cutting fluid (MCF2020). During testing, it was diluted with water to a concentration of 5 wt% and then subjected to performance testing. The testing methods and conditions were the same as in Example 1.
[0152] Comparative Example 4
[0153] Comparative Example 4 was a commercially available foreign brand microemulsion cutting fluid (Fuchs FS 68S). During testing, it was diluted with water to a concentration of 5 wt% and its performance was tested. The test methods and conditions were the same as in Example 1.
[0154] Performance Test 1
[0155] The working fluids prepared by adding water to the microemulsion water-based cutting fluids prepared in Examples 1, 2, 3, 5, and 10, as well as Comparative Examples 1, 2, 3, and 4, were tested for various indicators such as physicochemical properties, rust prevention, and corrosion prevention. The test results are shown in Table 1.
[0156] Table 1
[0157]
[0158]
[0159] As shown in Table 1, the microemulsion water-based cutting fluids of Examples 1-3, 5, and 10, and the copper specimens of Comparative Examples 1, 3, and 4, all achieved Grade A corrosion resistance, with better rust prevention performance than Comparative Examples 1-3, demonstrating excellent overall performance. The maximum non-seize load of Examples 1-5 was greater than that of Comparative Examples 1-3, and the maximum non-seize load of Example 10 reached 1667 N, indicating that the cutting fluid prepared by this invention has excellent lubrication and load-bearing capacity.
[0160] Performance Test 2
[0161] The stability test results were conducted according to GBT 6144-2010 and JBT 7453-2013, which are the criteria for evaluating the storage stability of cutting fluids at high and low temperatures. The specific test method was as follows: 20 mL of the cutting fluid stock solution was placed in a 100 mL stoppered graduated cylinder and placed in a constant temperature drying oven at 70℃±3℃ for 5 hours. After that, it was taken out and cooled to room temperature (15℃~35℃) for 3 hours. Then, it was placed in a low temperature environment at -12℃±3℃ for 24 hours. After that, it was taken out and allowed to stand for 1 hour to return to room temperature. The results were then observed to see if the fluid could return to its original state.
[0162] The microemulsion water-based cutting fluids prepared in Examples 1, 2, 3, 4, and 5, as well as Comparative Examples 1, 2, 3, and 4, were subjected to high and low temperature stability tests. The test results are as follows: Figure 1 As shown in the figure, it is clear that after the high and low temperature stability tests, no substances were precipitated in the stock solutions of Examples 1-5, and they could be restored to their pre-test state.
[0163] Performance Test 3
[0164] Friction performance test results:
[0165] 1. Figure 2 The maximum non-jamming load P on the workpiece is shown in Examples 1-5, Example 10, and Comparative Examples 1-4. B The test results show that the maximum non-seize load P in each embodiment of the present invention is... B The values are all greater than those of Comparative Examples 1-3, and the maximum non-seize load P of Example 5 is greater. B The value (1569N) is much greater than the maximum non-seize load P of Comparative Example 4 and Example 10. B The value can reach up to 1667N, indicating that the microemulsion water-based cutting fluid prepared by this invention has high lubrication carrying capacity.
[0166] 2. Figure 3 Examples 1-5 ( Figure 3 a) and Comparative Examples 1-4 Figure 3b) The friction coefficient curves. It can be seen that the friction coefficients of all embodiments of the present invention are below 0.1. The friction coefficients of Comparative Examples 1, 3, and 4 are comparable to those of the embodiments of the present invention, also below 0.1. However, the friction coefficient of Comparative Example 2 under the same test conditions is significantly higher than that of the embodiments of the present invention, indicating that the microemulsion water-based cutting fluid prepared by the present invention has superior lubrication performance.
[0167] 3. Table 1 shows the friction coefficient of long-distance wear measured by a four-ball friction tester, and Table 2 shows the wear scar diameter. Figure 4 The data shows that in Examples 1 to 5, the wear scar diameters were similar, and the wear scar surfaces were smooth and flat, indicating that the prepared microemulsion water-based cutting fluid has excellent anti-wear properties. Examples 6 to 10 show that increasing the concentration of the diluent or changing the load would cause a certain degree of change in the wear scar diameter.
[0168] Table 2
[0169]
[0170] 4. From the test results of the tapping torque values in Table 3, it can be seen that for copper alloys, the tapping torque values of the microemulsion water-based cutting fluids prepared in Examples 1-5 are comparable to those of Comparative Examples 1-4, indicating that the cutting fluids prepared in this invention can perform similarly to well-known domestic and foreign brands in terms of processing performance of copper alloys.
[0171] Table 3
[0172]
[0173]
[0174] In summary, this invention uses biodegradable vegetable oil and synthetic esters as composite lubricants, ammonium phosphate salts as anti-wear extreme pressure agents, and combines special amines and a combination of corrosion inhibitors with excellent anti-corrosion properties. By optimizing and adjusting the raw materials and preparation process, the resulting microemulsion water-based cutting fluid has good lubrication performance and high load-carrying capacity.
[0175] Compared with commercially available well-known domestic and international brands, the tapping torque values of the microemulsion water-based cutting fluid prepared by this invention are all lower than those of Fuchs (Ecocool 68S) and domestic brands (C800, SCC101A, MCF2020). Figure 5 The copper corrosion test results show that, after testing in Examples 1-5 and Comparative Examples 1, 3, and 4, the copper samples showed no color change, while Cu2+ precipitated in the solution of Comparative Example 2. Figure 6 The diluted sample showed a significant color change (turning blue). This indicates that the microemulsion water-based cutting fluid prepared in this invention exhibits excellent machining performance (rust prevention performance) when cutting copper alloy workpieces. Figure 7 & Figure 8 ), corrosion resistance and defoaming properties ( Figure 9 The microemulsion water-based cutting fluid of the present invention has significantly improved overall performance, is suitable for processing copper alloy workpieces, and has good application prospects.
Claims
1. A heavy-duty biodegradable microemulsion water-based cutting fluid specifically for copper alloys, characterized in that, It is prepared from the following raw materials in parts by weight: 4.0~8.0 parts of metal rust inhibitor; 10.0~18.0 parts of special amine; 5.0~10.0 parts of synthetic ester; 0.5~1.0 parts of extreme pressure agent; 5.0~10.0 parts of lubricant; and 0.5~1.0 parts of corrosion inhibitor. Dispersant 1.0~2.0 parts; bactericide 0.5~2.5 parts; Stabilizer 2.0~6.0 parts; Emulsifier 5.0~10.0 parts; 0.4-1.0 parts of anti-hardness agent; 45-50 parts of water.
2. The heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid as described in claim 1, characterized in that, The specific amine is one or more of the following: specific amine V-20, specific amine AMP-95, specific amine AM101, specific amine SA166, and diethylene glycol amine; The corrosion inhibitor is one or more of benzotriazole, alkyl phosphate, methylbenzotriazole, thiadiazole, and aluminum zinc magnesium corrosion inhibitor; The metal rust inhibitor is one or more of sebacic acid, phosphate ester, borate ester and dodecanoic acid; The lubricant is one or more of vegetable oil, base oil, naphthenic oil, polyether, and ethylene oxide-propylene oxide block copolymer; The dispersant is an alcohol ether carboxylic acid; The stabilizer is one or more of Tween 20, Tween 40, Tween 60, Tween 80, Span 20, Span 40, Span 60, and Span 80; The emulsifier is one or more of succinic anhydride amide, tallulamide, and talluldiethanolamide; The anti-hard water agent is tetrasodium ethylenediaminetetraacetate; The synthetic ester is one or more of the following: tetrameric castor oil ester, pentaerythritol oleate, trimethylolpropane oleate, trimethylolpropane coconut oil ester, diisooctyl sebacate, neopentyl glycol oleate, and isooctyl stearate. The bactericide is one or more of MBK, MBM, NS-MBM, MBO, BK, and BIT.
3. The heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid as described in claim 1, characterized in that, The extreme pressure agent is a phosphorus-nitrogen type extreme pressure anti-wear agent, specifically an ammonium phosphate salt, or a water-soluble phosphate ester.
4. The heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid as described in claim 3, characterized in that, The ammonium phosphate salt extreme pressure agent is prepared by the following steps: 1) A certain amount of isodecyl alcohol is added to the reaction vessel and pre-stirred. Phosphorus pentoxide and water are added and stirred continuously to prevent agglomeration. An esterification reaction occurs at a certain temperature to obtain a phosphate intermediate. 2) Then, alkylamine is added dropwise to the phosphate intermediate, and an amination reaction occurs at a certain temperature. Unreacted raw materials and byproducts are then removed by vacuum distillation to obtain ammonium phosphate salt.
5. The heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid as described in claim 4, characterized in that, In step 1), the water is tap water, and the amount used is 5wt%-10wt% of the total amount of isodecanol, phosphorus pentoxide, and water. In step 1), the pre-stirring temperature is 0-20℃ and the time is 10-30 min; In step 1), the esterification reaction is carried out at a temperature of 60-90℃ for 3-6 hours. In step 2), the amination reaction is carried out at a temperature of 100-130°C for 3-6 hours. In step 2), the vacuum distillation is carried out at a temperature of 80-130℃ for 0.5-1 hour. In step 2), the alkylamine is one or more of tertiary alkylamine, oleylamine, and dodecylamine.
6. The heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid as described in claim 4, characterized in that, The molar ratio of phosphorus pentoxide, isodecanol, and alkylamine used in the synthesis of the ammonium phosphate salt is 0.5-1:2-3:0.5-0.
9.
7. The preparation method of the heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1: Add special amine, metal rust inhibitor and a portion of water to the reactor, and heat and stir at 45~65℃ until the solution becomes clear; S2: Add the emulsifier, extreme pressure agent, lubricant and synthetic ester to the solution obtained in step S1, and continue heating and stirring until the solution becomes clear; S3: Add the stabilizer and the anti-hard water agent to the solution obtained in step S2, and continue heating and stirring until the solution becomes clear; S4: After the temperature of the solution obtained in step S3 drops to 10~35℃, add the dispersant and bactericide to the solution and stir until transparent; S5: Add the corrosion inhibitor to the solution obtained in step S4, stir until transparent, add another part of water, mix and stir to obtain microemulsion water-based cutting fluid.
8. The preparation method according to claim 7, characterized in that, In step S1, the stirring temperature is 50~60℃ and the stirring time is 0.2~1 h; In step S2, the stirring temperature is 45~65℃ and the stirring time is 0.2~1 h; In step S3, the stirring temperature is 45~65℃ and the stirring time is 0.2~1 h; In step S4, the stirring temperature is room temperature; the stirring time is 0.2~1 h; In step S5, the stirring time until transparent is 0.2~0.5 h, and the temperature is 55~65℃; the mixing time is 0.5~1 h.
9. The preparation method according to claim 7, characterized in that, The heavy-duty copper alloy-specific biodegradable microemulsion water-based cutting fluid can be diluted with tap water or well water to form a working fluid before use. When diluting, the cutting fluid is diluted with water to a working solution with a concentration of 5-20 wt%, preferably 5 wt%, 10 wt%, or 20 wt%.
10. The application of the heavy-duty copper alloy biodegradable microemulsion water-based cutting fluid according to any one of claims 1 to 6 in metal cutting or grinding processes.
Citation Information
Patent Citations
Metal working fluid for copper alloy
CN104450097A
Water-soluble metal working fluid for aerospace composite materials and preparation process of water-soluble metal working fluid
CN117229839A
Copper alloy metal working fluid and preparation method thereof
CN118853270A